2016
DOI: 10.1177/0956462416653510
|View full text |Cite
|
Sign up to set email alerts
|

Rectal chlamydia – should screening be recommended in women?

Abstract: Chlamydia trachomatis is the most common bacterial sexually transmitted infection in Europe and has large impacts on patients' physical and emotional health. Unidentified asymptomatic rectal Chlamydia trachomatis could be a partial explanation for the high Chlamydia trachomatis prevalence. In this study, we evaluated rectal Chlamydia trachomatis testing in relation to symptoms and sexual habits in women and men who have sex with men. Rectal Chlamydia trachomatis prevalence was 9.1% in women and 0.9% in men who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Linkage of patient records would allow studies examining whether the association between faster natural clearance of infection and lower rates of reinfection, reported by Geisler et al [ 42 ] for mostly African American women in a sexually transmitted disease clinic setting, occurs in other populations. Additionally, as the gastrointestinal tract may be an important reservoir for chlamydia infection in women because of the possibility of autoinfection [ 43 , 44 ], rectal testing could be used to obtain estimates of the duration of rectal infection. A strength of the Bayesian approach that we have used is that different types of information can be incorporated as they become available to improve estimates in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage of patient records would allow studies examining whether the association between faster natural clearance of infection and lower rates of reinfection, reported by Geisler et al [ 42 ] for mostly African American women in a sexually transmitted disease clinic setting, occurs in other populations. Additionally, as the gastrointestinal tract may be an important reservoir for chlamydia infection in women because of the possibility of autoinfection [ 43 , 44 ], rectal testing could be used to obtain estimates of the duration of rectal infection. A strength of the Bayesian approach that we have used is that different types of information can be incorporated as they become available to improve estimates in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the prevalence of these genotypes differ by anatomical site and sexual network. Genotypes D and G are more commonly detected in the anorectal tract and, along with genotype J, are prevalent in women and men who have sex with men (MSM) [8][9][10][11][12][13][14][15] . Genotypes D, E, and F are found in the majority of urogenital infections and are common among heterosexuals 8,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Management and control of CT infection remain continuously challenging [4,19]. Reasons are likely manifold, but there is prominent discussion about the potential importance of rectal CT infection in women in particular [20,21]. Asymptomatic rectal CT has been hypothesized to be a reservoir of untreated infection, hindering chlamydia control [22].…”
Section: Chlamydia-critical Gaps In Knowledgementioning
confidence: 99%